Long Chan soda beverage / Ammar Mustaqim Zuhadi - Zuhadi, Ammar Mustaqim (2022)
The main objective of this project is to reinforce the Long Chan Soda Product Beverage to be on par with other famous brand in the market and have strong brand connection among the locals.